Analysis of the morphometric change in the uncinate process of the cervical spondylosis patients: A study of radiological anatomy - Shangbin Cui; Al-Attar E. Nasser; Ling Ma; Peiqiang Su; Deying Su; Zhiheng Liao (Journal of Orthopaedic Translation, 2020)
Purpose: Although there are many researches that focus on the relationship between the vertebral artery and uncinate process (UP), there were no publications concerning difference in the dimensions of the UP between the normal spine and degenerative spine, especially in Chinese patient. The purpose of this study is to determine the anatomic parameters that can be used as a guide for the procedure in intervertebral foramen decompression and for analysis of the morphometric change in the UP of the cervical spondylosis patients. Methods: Forty patients from January 2016 to January 2019 were enrolled in this study. Three-dimensional computed tomography scans of the cervical spine were performed. The patients were subdivided into two groups which were nondegenerative cervical spine group (20 cases) and degenerative cervical spine group (20 cases). Six parameters concerning the height, width and angle of the UP were measured. Results: In nondegenerative group, the average pedicle width was 3.63 mm–5.91 mm from C3 to C7. The average width of safe UP resection will be 3.06 mm at C3, 3.12 mm at C4, 3.28 mm at C5, 2.74 mm at C6 and 2.01 mm at C7. The average safe depth will be 6.04 mm at C3, 6.52 mm at C4, 7.61 mm at C5, 6.07 mm at C6 and 5.09 mm at C7. There are statistic difference between degenerative group and nondegenerative group, especially in the parameter minimum height of UP, maximum height of UP, medial border's distance of UP and later border's distance of UP. Conclusion: In this retrospective study, our results suggest that for the Chinese patients who suffered from cervical spondylosis could be performed intervertebral foraminotomy decompression by resecting part of the UP. The safe range within the spinal canal was up to 6.73 mm of width between inferior vertebral endplate and superior vertebral endplate in the intervertebral space and up to 5.09 mm of depth from medial border of the UP to the lateral side atC3 to C7 without interfering the spinal nerve root and vertebral artery. The translational potential of this article: Our study found the safe margin to perform intervertebral foramen decompression to the UP for the cervical spondylosis patients. This may help to improve safeness of the surgical procedure and provide data for future robotic surgery.